FEATURES OF GRAVIMETERS IN MODERN GRAVIMETRIC SYSTEMS - BEZVESILNA, Olena; GRYNEVYCH, Mariia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper reviews modern gravimeters of aviation gravimetric systems, their design and principle of operation. Their advantages and disadvantages, features of their functioning and processing of the received data are analyzed. It is shown that high-precision measurements of gravitational acceleration (g) are extremely relevant and necessary for many fields of science and technology. The main characteristics of known aviation gravimeters are given. It has been established that known aviation gravimeters have insufficient accuracy (2-10 mGal). Under the action of the g, the armature moves down inside the magnetic circuit and causes a change in the electromagnetic flux. Under the action of an external electromagnetic flow of an obstacle, this flow will induce two EMF obstacles in two sections, which are included in series-opposite. The total effect of these errors on the output signal of the gravimeter-invention will be zero. The mutual connection of the sections provides cancellation of errors due to the influence of external electromagnetic flows, which can be significant when installing the gravimeter on such a moving object as an airplane. In the same way, the device works under the action of the main obstacle for aviation gravimeters of the vertical acceleration of the aircraft, the errors due to the influence of which are cancelled in the TG. In TG, the residual instrumental errors are cancelled, since they will have opposite signs in the two measuring channels of the two sections of the secondary winding, which are connected oppositely. It is shown that the new TG has significantly greater accuracy than known aviation gravimeters due to the cancellation of errors due to the effects of vertical acceleration of the aircraft, external electromagnetic fields, and residual instrumental errors. It is substantiated that the new TG has significantly greater accuracy than known aviation gravimeters due to the cancellation of errors due to the influence of the vertical acceleration of the aircraft, the influence of external electromagnetic fields, and the influence of residual instrumental errors.
Keywords: gravimeter; gravimetric systems; aviation; gravitational acceleration; Earth's gravitational field